Over the wall/after the fall : post-communist cultures through an East-West gaze - Forrester, Sibelan E. S. (Sibelan Elizabeth S.); Zaborowska, Magdalena J.; Gapova, Elena (Indiana University Press, 2004)
" ... A hot subject in today's scholarship ... and a groundbreaking project of vital significance to the field of cultural studies at both 'western' and 'eastern' geographical locations."--Elwira GrossmanOver the Wall/After the Fall maps a new discourse on the evolution of cultural life in Eastern Europe following the end of communism. Departing from traditional binary views of East/West, the contributors to this volume consider the countries and the peoples of the region on their own terms. Drawing on in